Developing an Integrated Learning Assessment Model for Junior High School Students - Indana, Sifak; Wasis, Wasis; Suyono, Suyono; Rahaju, Endah Budi (FKIP Universitas Lampung, 2022)
Developing integrated learning assessment model for junior high school students. Objective: This study aims to produce a valid and practical assessment model for integrated learning at the junior high school level. Method: This research is development research. Research respondents came from 6 junior high schools in Surabaya with a total of 211 students. The instruments used are validation sheets, observation sheets, and questionnaires. Findings: The results showed that (1) the developed assessment model and instrument were in the valid category, both in construction and in substance; (2) Practical, appropriate and able to be applied in integrated learning in junior high schools; (3) The test results show that the competence of knowledge-understanding and application is relatively high. Conclusion: The developed assessment models and instruments are feasible to be applied in integrated learning and are found to be more interesting, fun, and useful for junior high school students. Keywords: developing, assessment model, integrated learning, junior high school.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202221